Strengthening Governance and the Rule of Law in Postconflict Societies: A Comparative Doctrinal Study of the Chemmani Mass Grave Investigations in Sri Lanka and Argentina - Umaibalan, V. (Faculty of Arts, University of Jaffna & Surana and Surana International Attorneys, 2026)
In post-conflict societies, the investigation of mass graves constitutes a critical test of governance and the rule of law. This paper examines whether Sri Lanka’s legal and institutional response to the Chemmani mass grave investigations in Jaffna has complied with core rule-of-law requirements, namely legality, equality before the law, judicial accountability, and effective remedies. The Chemmani case, first revealed during criminal proceedings in 1998, serves as a focused case study of post-conflict criminal justice administration. Adopting a doctrinal methodology, the paper analyses the obligations imposed on investigative and judicial authorities under the Code of Criminal Procedure Act No. 15 of 1979, including duties relating to police investigations, magisterial supervision, and inquests into suspicious deaths. It further evaluates compliance with Articles 11, 12(1), and 13 of the Constitution of Sri Lanka, which guarantee freedom from torture, equality before the law, and due process, as well as Sri Lanka’s international obligations under the International Covenant on Civil and Political Rights Act No. 56 of 2007. The study demonstrates that prolonged investigative delays, limited prosecutions, inadequate witness protection, and weak judicial oversight in the Chemmani case represent a departure from rule-of-law standards and undermine public confidence in post-conflict governance. For comparative insight, the paper draws on Argentina’s post-dictatorship experience in investigating mass graves and enforced disappearances, particularly the role of judicially supervised investigations, independent forensic mechanisms, and sustained prosecutions in restoring accountability. The core argument advanced is that Sri Lanka’s failure lies not in the absence of legal norms, but in deficient institutional enforcement. The paper concludes by proposing doctrinal reforms aimed at strengthening judicial supervision and prosecutorial independence to reinforce the rule of law in post-conflict Sri Lanka.
Keywords: Rule of law; Post-conflict governance; Mass grave investigations; Judicial accountability; Comparative constitutional law